Growth Acceleration Strategy Sharia Regional Development Banks (BPD) In Indonesia - Irmayani; Anfa, Sugianto; Anggraini, Tuti (PT Mattawang Mediatama Solution, 2024)
This study aims to formulate the core problem by choosing what is the best strategic alternative that can be taken by Islamic business units to accelerate the growth of the Islamic banking industry. By exploring aspects of internal and external problems. Then the solution from internal and external of various acceleration strategies based on expert opinion related to the phenomenon of the researcher's problem. This research methodology is descriptive qualitative with a quantitative approach and research using ANP (Analytic Network Process) analysis tools. In this study using experts totaling 5 people consisting of academics, practitioners and regulatory experts. The results of this study indicate that: 1). There are two main problems, namely external and internal problems. The most prioritized problem in determining the acceleration strategy is the external problem with an average combined value of 53%, while for the W (Rater Agreement) value of all respondents is 0.36. The most prioritized external problem is the problem of local government support with an average value of 35% with a Rater Agreement of all respondents of 0.64, while the priority problem in internal problems is the problem of capital. 2) for the most prioritized solution, namely the external solution with a combined average value of 54%, while for the W (Rater Agreement) value of all respondents is 1. In the most prioritized external solution, namely local government support, the W (Rater Agreement) value is 0.84. With an average value of 35%. 3. The most prioritized strategy is conversion with an average value of 26%, while for the marger, spin off and acquisition strategies it is around 25%, with a W (Rater Agreement) value of 0.46, meaning that the answers of the respondents have moderate agreement.